My life on mountain railroads - Gould, William John Gilbert, author; Gould, William R., editor; Utah State University Press, publisher (Colorado State University. Libraries, 1995)
In 1917, Gilbert Gould achieved his dream to be an engineer, and began running engines for the Denver & Rio Grande and later for the Utah Railway. He was a natural storyteller, and his recollections are entertaining and historically rewarding.
Youth -- Trackside childhood -- From newsboy to roundhouse: starting to work -- Fireman I -- Learning to fire -- Life along the rails -- My mentor on the road -- Fireman II -- At the rat hole flashing the door -- Old heads, rails, and boomers -- Railroad hazards and wrecks -- Engineer -- Engineer on the Rio Grande -- Running the Utah trains -- Life on the Utah Railway.
Keywords: Mountain railroads -- Utah -- History; Mountain railroads -- Utah -- Employees -- Biography; Gould, William John Gilbert, 1888-1961